CONJUNCTIVE RELATIONS IN EFL LEARNERS’ WRITINGS AND NEWSWEEK’S ARTICLES - Ambalegin Ambalegin; Tomi Arianto (IdeBahasa, 2019)
This study investigated the conjunctive relation use theorized by Halliday & Matthiessen (2014) in the EFL learners’ writings of Putera Batam University and articles Newsweek magazines printed in 1998. This descriptive qualitative study found out the frequency of the semantic categories of conjunctive relation namely adversative, additive, temporal, and causal types used to link the words, phrases, clauses, sentences, and paragraphs semantically and logically in both writings. Method of identification is used to collect the data from 42 essay writings and 24 articles. This study used distributional method to analyze whereas they were selecting, sorting, categorizing, and differencing ways to get the each type of conjunction. Results of the study showed that the EFL learners’ writings appeared and as the most frequent and but was the most frequent appearance in Newsweek’s articles. Newsweek’s articles used 33 different items of conjunctive relation meanwhile the EFL learners’ writings used 26 different items of conjunctive relation. The adversative type (48, 91%) is the dominant frequency in the Newsweek’s articles and the additive type is dominant frequency in the EFL learners’ writings. EFL learners did not apply a various types of conjunctive relations but the Newsweek’s articles did. In addition, EFL learners used too over and as found 546 times in their writings.